골다공증의 한방 복합 처방 및 단일 본초에 대한 국내 연구 고찰 - 2013년 이후 발표된 국내 연구를 중심으로 - 이정민(Jung Min Lee); 김남훈(Nam Hoon Kim); 이은정(Eun-Jung Lee) (동의생리병리학회지, 2021)
The purpose of this study was to investigate the effect of single herbal medicines and Korean herbal medicine complex prescriptions for osteoporosis in Korea. We targeted studies published in domestic journals from January 1, 2013 to April 1, 2021. For domestic databases, RISS, NDSL, OASIS, DBpia, KISS, KISTI, and Korean Traditional Knowledge Portal were used. Words such as "osteoporosis", "herbal medicine", "herbal combination prescription" and "herbal" were combined and searched. A total of 32 studies were selected. Among them, 8 studies were conducted exclusively for animal studies, 18 studies were conducted on cell experiments, and 6 studies were conducted on both animal and cell experiments. There were 18 studies using a single herb and 14 studies using a combination of Herbal medicine. As a result of the investigation of a single herb, it was found that 補陽藥 was most widely used, and it was found that it was mainly used in the herbal combination prescription, mainly for 補陽藥, 補氣藥, and 補陰藥. Studies in animal experiments revealed significant results mainly in bone mineral density, serological indicators, and morphological indicators of bone tissue. In the study of cell experiments, the effects were found in factors related to the differentiation of osteoclasts and inhibitors of inflammation. Through the results of this study, we are able to confirm the effective single herbal medicines and herbal medicine complex prescriptions for the treatment of osteoporosis, and it is expected that they will contribute to clinical treatment.